Majority support of shareholders, monitoring incentive, and dividend policy - Mori, Naoya; Ikeda, Naoshi (Journal of Corporate Finance, 2015)
As an alternative version of the side-payment model, this paper presents a demonstration of how the necessity of winning majority support of shareholders influences the relation between a blockholder's monitoring incentive and a firm's dividend policy. When dividend-averse individuals collectively hold a majority stake in a dispersed ownership structure, a dividend-seeking blockholder might be compelled to propose lower dividends than the tax-optimum to dominate the zero-dividend proposal. Under such circumstances, the blockholder has an incentive to provide unprofitable monitoring activity as long as the private benefits of tax-saving are greater than the pecuniary loss from the monitoring activity.